Hambor as Little Narrative in Managing Conflict and Peace Situation in Manggarai, Flores, East Nusa Tenggara - Maksimilianus Jemali; JB Banawiratma; Wening Udasmoro (UNHI PRESS, 2021)
This article explores the practice of Hambor tradition as little narrative in managing conflict and peace situations in Manggarai, Eastern Indonesia. Hambor, which means peace, is a component of local wisdom and a strategy for resolving conflict based on local culture. There are several issues to address, including the following: what is the meaning, impact, and manifestation of Hambor for Manggarai people on a personal and social level? What is the role of Hambor tradition in managing conflict and peace in Manggarai? This research used the ethnographic method through the genetic structuralism approach developed by the French philosopher and sociologist Pierre Bourdieu to understand the meaning, impact, and implementation of the Hambor process in daily life by the Manggaraian speech community. The research result shows that Hambor is the leading force in creating peace and harmony for the Manggarai people. Hambor is the substance of harmony between humans, the world (tana lino), the ancestors (wura agu ceki), and the God (Mori KraÃ©ng). Hambor process in Manggarai will be useful if it is based on a mutual commitment to overcoming disputes, transformative option (post-conflict), and the involvement and willingness of perpetrator and victim to forgive one another.